MENINGKATKAN KETERAMPILAN MENULIS KARANGAN NARASI MELALUI PENERAPAN STRATEGI GUIDED NOTE TAKING PADA SISWA KELAS IV DI SD NEGERI 1 KAOBULA - Kamasiah, Kamasiah (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2021)
This study aims to determine the improvement of narrative essay writing skills through guide note taking strategies for fourth grade students of SD Negeri 1 Kaobula. The type of research conducted by the researcher is classroom action research (CAR). The results showed that the average value of each of these aspects can be seen that the narrative essay writing skill has not met the target of achieving a score of 75.00 in the class average. The average score of 50.3 comes from the total score of each narrative essay writing skill. The average value of narrative essay writing skills using the Application of Guided Note Taking Strategy is 63.79 and is included in the sufficient category. 86% of students also have not reached the KKM, which is 70. So, the target for a class average of 75 with good categories still cannot be achieved. For this reason, researchers will follow up with learning in cycle II. The average value achieved in the second cycle is 78. The average value has met the classical average value to be achieved, which is 78. Then the percentage results that reach a value > 90 in the very good category are 1 student or 4, 17%, then the value of students who reach a value of 80-90 with a good category of 12 students or 50%, then the value of students who get a value of 60-70 with a sufficient category of 11 respondents or 45.84% and the value of students who get a value of 40-50 with the less category, no students get that value.